Ecologia de fragmentos de floresta estacional decidual ripária: fitossociologia, dinâmica e relações ambientais - Andrzejewski, Camila (2020)
Degraded forest landscapes are recurrent in the Atlantic Forest Biome, where small fragments predominate. These ecosystems still hold rich biodiversity associated with different relief landscapes, where the shrub-tree vegetation may have a structure determined by specific environmental conditions. Riparian forests are examples of ecosystems where small variations in relief associated with the hydrological regime determine floristic and structural heterogeneity in communities. In this context, the general objective of this thesis was to identify the influence of environmental factors on vegetation, variations in dynamics and to determine the occurrence of environmental sectors in riparian fragments of Seasonal Decidual Forest, located on the banks of the Ijuí River, in the northwest region of Rio Grande do Sul. The hypotheses and objectives of the proposed chapters are as follows: i) communities and populations in the tree strata have differences in structure and growth over a period of four years; ii) floristic changes occur in the regenerating and structural community at the population level in a short period; iii) riparian forest vegetation has variation associated with different environmental sectors; iv) evaluate the dynamics of shrub-tree vegetation in different environmental sectors. For the study, vegetation was monitored from 2015 to 2019 in three classes: Arboreal Stratum (AS) - diameter at chest height (DBH, measured at 1.30 m above ground) ≥ 5 cm; Established Regeneration (RE) - 1 cm ≤ DBH <5 cm; Seedlings (Pl) - DBH <1 cm and height ≥ 20 cm. 36 plots of 10 m x 20 m for AE, 5 m x 10 m subplots were used to evaluate the RE and 3.16 m x 3.16 m subplots to measure the Seedling class. The tree strata had little significant fluctuations in density, in the proportion of individuals and species of each ecological group. Light-demanding climatic had a greater representation in the number of species and individuals and that of the diametric distribution of the tree comunity indicated that it is capable of perpetuating itself. In the regeneration classes, it was found a reduction in the number of individuals and diversity, and for RE there was an increase in the density of climatic species tolerant to shade, as well as of autochorous species. Considering the environmental variables, four environmental sectors were determined: Sector I, classified with the largest canopy opening; Sector II, with higher levels of zinc and organic matter; Sector III, consisting of the parcels with the highest elevation and the lowest canopy opening; Sector IV grouped by aluminum saturation, which presented the lowest diametric amplitude and the highest concentration of individuals in the initial classes of EA and the lowest density in class Pl. The results obtained show the environmental heterogeneity in riparian forests and their relationship with the structure and vegetation dynamics, exposing the need to support biodiversity conservation practices and ecosystem services in environmental sectors.